The osteology of Ferrodraco lentoni, an anhanguerid pterosaur from the mid-Cretaceous of Australia. Issue 5 (30th March 2022) - Pentland, Adele H.; Poropat, Stephen F.; White, Matt A.; Rigby, Samantha L.; Bevitt, Joseph J.; Duncan, Ruairidh J.; Sloan, Trish; Elliott, Robert A.; Elliott, Harry A.; Elliott, Judy A.; Elliott, David A.
ABSTRACT: Ferrodraco lentoni, an anhanguerid from the Upper Cretaceous Winton Formation of northeast Australia, is the most complete Australian pterosaur described to date, represented by a partial cranium, incomplete cervical series and wing elements. Herein we present a comprehensive osteological description of Ferrodraco, as well as an emended diagnosis for this taxon. In addition, we compare Ferrodraco with other isolated pterosaur remains from Australian Cretaceous deposits. Subtle, yet salient, differences indicate that at least three of these specimens, all derived from the upper Albian Toolebuc Formation, are distinct from Ferrodraco . However, we are uncertain whether these specimens are attributable to Mythunga camara, Aussiedraco molnari, Thapunngaka shawi, or an as yet un-named taxon. Detailed description of the postcranial material of Ferrodraco also provides an opportunity to reassess its phylogenetic position. In one analysis, Ferrodraco and Mythunga are resolved as sister taxa within Tropeognathinae, whereas in another, Ferrodraco, Mythunga, and Tropeognathus form a polytomy within Coloborhynchinae. Either way, these slight differences notwithstanding, a close relationship between Ferrodraco and Mythunga is evident, supporting the interpretation that they form a clade. By contrast, Aussiedraco molnari is resolved as a member of Targaryendraconia, a clade with a cosmopolitan distribution. The presence of several anhanguerian taxa or lineages in the late Early and early Late Cretaceous of northeast Australia is suggestive of even greater diversity in the Australian pterosaur fauna.